Ovalbumin-specific CD4+ and CD8+ T cells contribute to different susceptibility for Theiler’s murine encephalomyelitis virus persistence - Wannemacher, Rouven; Reiß, Anna; Rohn, Karl; Lühder, Fred; Flügel, Alexander; Baumgärtner, Wolfgang; Hülskötter, Kirsten (Frontiers in Immunology, 2023)
Theiler’s murine encephalomyelitis virus (TMEV) is the causative agent of TMEV-induced demyelinating disease (TMEV-IDD); a well-established animal model for the chronic progressive form of human multiple sclerosis (MS). In susceptible mice with an inadequate immune response, TMEV-IDD is triggered by virus persistence and maintained by a T cell mediated immunopathology. OT-mice are bred on a TMEV-resistant C57BL/6 background and own predominantly chicken ovalbumin (OVA)-specific populations of CD8+ T cells (OT-I) or CD4+ T cells (OT-II), respectively. It is hypothesized that the lack of antigen specific T cell populations increases susceptibility for a TMEV-infection in OT-mice on a TMEV-resistant C57BL/6 background. OT-I, OT-II, and C57BL/6 control mice were infected intracerebrally with the TMEV-BeAn strain. Mice were scored weekly for clinical disease and after necropsy, histological and immunohistochemical evaluation was performed. OT-I mice started to develop progressive motor dysfunction between 7 and 21 days post infection (dpi), leading up to hind limb paresis and critical weight loss, which resulted in euthanasia for humane reasons between 14 and 35 dpi. OT-I mice displayed a high cerebral virus load, an almost complete absence of CD8+ T cells from the central nervous system (CNS) and a significantly diminished CD4+ T cell response. Contrarily, only 60% (12 of 20) of infected OT-II mice developed clinical disease characterized by mild ataxia. 25% of clinically affected OT-II mice (3 of 12) made a full recovery. 5 of 12 OT-II mice with clinical disease developed severe motor dysfunction similar to OT-I mice and were euthanized for humane reasons between 13 and 37 dpi. OT-II mice displayed only low virus-immunoreactivity, but clinical disease correlated well with severely reduced infiltration of CD8+ T cells and the increased presence of CD4+ T cells in the brains of OT-II mice. Though further studies are needed to reveal the underlying pathomechanisms following TMEV infection in OT mice, findings indicate an immunopathological process as a main contributor to clinical disease in OT-II mice, while a direct virus-associated pathology may be the main contributor to clinical disease in TMEV-infected OT-I mice.